The effect of hepatitis B vaccination after five years on an entire population in an insular region of Southeast China - Ying Liu; Jingjing Ren; Zikang Wu; Lingzhi Shen; Huan Shan; Xuewei Dai; Jing Li; Yan Qiu; Wen Ren; Jun Yao; Lanjuan Li (Taylor & Francis Group, 2021)
Prevalence of hepatitis B (HB) remains high among adults in insular regions of southeast China. To address this issue, large-scale HB vaccination was implemented in Putuo County of Zhoushan City in 2013. To examine the effects of this large-scale HB vaccination, a cross-sectional serological survey was conducted on two isolated islands, Putuo (intervention group) and Dinghai (control group) Counties of Zhoushan City in southeastern China five years later. The data showed lower prevalence of HBsAg and negative results for all HBV markers in the intervention group compared to the control group (4.2% and 6.0%, 20.8% and 33.0%), while the positive rate for anti-HBs and only anti-HBs were higher (68.4% and 53.4%, 47.9% and 34.3%). Therefore, large-scale adult HB vaccination could lower the HB epidemic level. However, the proportion of susceptible people who were negative for all HBV markers remained high. Hence, several additional measures to limit the spread of HBV should be taken by the government.